Percepción de los docentes hacia el proceso de inclusión de estudiantes con necesidades educativas especiales en aulas multigrado del municipio de Uribia, La Guajira. - Barliza Ipuana, Jessica (Universidad Antonio Nariño, 2021)
The purpose of this study was to identify the perceptions of the elementary school teachers of the Center Ethnoeducativo Rural Integral (CEIR) Katanaman towards the inclusion of boys, girls and young people with SEN in multigrade classrooms. The research included the participation of the 8 professors who they currently work in elementary school. The methodology used to achieve the objectives was quantitative research, a questionnaire was applied to the participants through a Google form that featured 12 statements about how teachers understand the inclusion, but also this author sought to know results are the main obstacles to implement inclusion in multigrade classrooms.